Evaluation of phosphorus requirement and calcium to phosphorus ratio in nursery and finishing pigs and stability of phytases - Vier, Carine Mirela (Kansas State University, 2019)
This dissertation consisted of 6 chapters involving studies with standardized total tract digestible (STTD) phosphorus (P) requirements of nursery and finishing pigs, dietary calcium (Ca) to P ratio, economic model for optimum P level, stability of phytases, and reproducibility of research results. Chapter 1 describes 2 experiments that evaluated the STTD P requirements of nursery pigs fed diets without or with 1,000 phytase units (FYT). These data provided empirical evidence that for 11- to 23-kg pigs, the NRC (2012) accurately estimates the STTD P requirement on a g/d basis. As a percentage of the diet, the STTD P requirement for diets without or with 1,000 FYT added phytase ranged from 0.34 to 0.42% to maximize average daily gain (ADG) and gain:feed ratio (G:F). Chapter 2 characterized a dose response to increasing STTD P concentration in diets for 24- to 130-kg pigs. The digestible P requirements to maximize ADG and G:F were 122 and 116% of NRC (2012) estimates across dietary phases, respectively. A greater STTD P of 131% of NRC (2012) estimates, was required to optimize bone mineralization. The third chapter consisted of two experiments to determine the effects of Ca:P ratio in diets adequate in STTD P on performance of 26- to 127-kg pigs fed diets without or with 1,000 FYT added phytase. The maximum responses in ADG, hot carcass weight, and bone ash were estimated at 1.63:1, 1.11:1 to 1.60:1, and 1.25:1 analyzed Ca:P and at 1.75:1, 1.28:1 to 1.71:1, and 1.40:1 STTD Ca:STTD P, respectively. Moreover, expressing ADG on a STTD Ca:STTD P basis provided a more consistent estimate of the ideal Ca:P ratio among the two studies than analyzed Ca to analyzed P ratio. The study presented in chapter 4 described a Microsoft Excel®-based P economic tool. This tool was developed based on the information generated in the above chapters. The objective of the tool is to contrast current dietary STTD P concentrations to recommended values that yield maximum growth performance while accounting for financial implications over different scenarios. In chapter 5, an experiment was conducted to evaluate the effects of storing three commercially available phytase products over 90 d under high temperature and high humidity conditions on phytase stability, growth performance, bone mineralization, and serum myo-inositol concentration of nursery pigs. Residual phytase activity decreased as storage time increased, and when phytases were stored in a vitamin and trace mineral premix compared to pure form. Except for HiPhos in pure form, bone ash was reduced when phytases were stored for 90 d compared to a positive control diet with no added phytase. Finally, chapter 6 focuses on reproducibility of research results in the animal sciences from the aspects of making the raw data available, documenting the statistical model, and reporting that is integrated with the statistical analysis. Several reproducible research tools are presented to make data and code publicly accessible in a data repository, and to generate dynamic reports that accurately describe the steps involved in generating the research findings.
Keywords: Calcium; Digestible phosphorus; Modeling; Phytase; Swine